Mortality outcomes associated with invasive aspergillosis among acute exacerbation of chronic obstructive pulmonary disease patient population. (January 2022) - Mir, Tanveer; Uddin, Mohammed; Khalil, Amir; Lohia, Prateek; Porter, Lekiesha; Regmi, Neelambuj; Weinberger, Jarrett; Koul, Parvaiz A.; Soubani, Ayman O.
Abstract: Background: Literature regarding trends of mortality, and complications of aspergillosis infection among patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is limited. Methods: Data from the National Readmissions Database (NRD) that constitutes 49.1% of the stratified sample of all hospitals in the United States (US), representing more than 95% of the national population were analyzed for hospitalizations with aspergillosis among AECOPD. Predictors and trends related to aspergillosis in AECOPD were evaluated. A Linear p-trend was used to assess the trends. Results: Out of the total 7, 282, 644 index hospitalizations for AECOPD (mean age 69.17 ± 12.04years, 55.3% females), 8209 (11.2/10, 000) with primary diagnosis of invasive aspergillosis were recorded in the NRD for 2013–2018. Invasive aspergillosis was strongly associated with mortality (OR 4.47, 95%CI 4.02–4.97, p < 0.001) among AECOPD patients. Malignancy and organ transplant status were predominant predictors of developing aspergillosis among AECOPD patients. The IA-AECOPD group had higher rates of multi-organ manifestations including ACS (3.7% vs 0.44%; p-value0.001), AF (20% vs 18.4%; p-value0.001), PE (4.79% vs1.87%; p-value0.001), AKI (22.3% vs17.5%; p-value0.001), ICU admission (16.5% vs11.9%; p-value0.001), and MV (22.3% vs7.31%; p-value0.001) than the AECOPD group. The absolute yearly trend for mortality of aspergillosis was steady (linear p-trend 0.22) while the yearly rate of IA-AECOPD had decreased from 15/10, 000 in 2013 to 9/10, 000 in 2018 (linear p-trend 0.02). Interpretation: Aspergillosis was related with high mortality among AECOD hospitalizations. There has been a significant improvement in the yearly rates of aspergillosis while the mortality trend was steady among aspergillosis subgroups. Improved risk factor management through goal-directed approach may improve clinical outcomes. Highlights: AECOPD patients with invasive aspergillosis had higher in-hospital mortality rates compared to those without invasive aspergillosis (14.5% vs 3.6%; p-value <0.001). In a multivariate logistic regression analysis, aspergilosis was highly associated with malignancy and organ transplant. In a multivariate logistic regression analysis, age and underlying cancer were associated with higher mortality among invasive aspergillosis patients. The absolute yearly rate of IA-AECOPD had decreased, however, the yearly mortality rate was steady.